FORGIVENESS, GRATITUDE AND PSYCHOLOGICAL WELL-BEING AMONG CARE GIVERS OF MENTAL DISORDER PATIENTS - Syeda Banin Zehra Taqvi; Shajeea Sheraz Kanjiani; Dr. Ghazala Fazaldad; Sufia Azad; Haleema Adnan (International Journal of Contemporary Issues in Social Sciences, 2024)
This study explores the relationships among forgiveness, gratitude, and psychological well-being in caregivers of patients with mental disorders. Utilizing a quantitative research design, the study involved a sample size of 200 caregivers from various mental health facilities. The population consisted of individuals aged 24-35 who provide care to patients diagnosed with various mental health conditions, ensuring a diverse representation of caregiving experiences. Data were collected using validated instruments: The Heartland Forgiveness Scale to measure forgiveness, the Gratitude Questionnaire-6 to assess gratitude levels, and the Psychological Well-Being Scale to evaluate overall well-being. Statistical analyses, including correlation and regression analyses, were conducted to examine the interplay among the variables. Results indicated significant positive correlations between forgiveness and psychological well-being, as well as between gratitude and psychological well-being, suggesting that higher levels of forgiveness and gratitude contribute to enhanced mental health outcomes among caregivers. Additionally, the study highlighted the mediating role of gratitude in the forgiveness-well-being relationship, indicating that caregivers who cultivate gratitude may experience greater psychological well-being. These findings underscore the importance of fostering emotional strengths in caregivers, suggesting that interventions aimed at enhancing forgiveness and gratitude could significantly improve their psychological well-being. This research contributes to the existing literature by providing empirical evidence of the interconnectedness of these constructs within the caregiving context, ultimately informing mental health practices and caregiver support programs.